Measurement of the moisture content of the slipper in the production of ceramic mass using the Capacitive Soil Moisture Sensor (Texas Journal of Engineering and Technology, 2023)
In this article, the method of measuring the moisture content of the slurry using the Capacitive soil moisture sensor in the production of porcelain is considered and a scheme is developed